ENVIRONMENTAL DEGRADATION AND ECO-DHAMMA: SOLUTION ACCORDING TO THE BUDDHIST POINT OF VIEW - Sayekti, Rina; Sugeng, Sugeng; Purnama, Ita; Widiyono, Widiyono (Jurnal Pencerahan, 2022)
The purpose of this study is to provide solutions to reduce environmental degradation. The solution to reducing environmental degradation according to the Buddhist view in associated with the Sutta in the Nikāya. The concept of Eco-dhamma, which concerns reciprocity, cause, and effect, and the interdependent relationship between beings and their environment used called the literature by collecting library materials that are coherent with the object of discussion. The collected data will be processed by: (a) editing; (b) organizing; and c) finding research results. The writing team performed data analysis of the used a symthesis checklist consisting of a data synthesis of introduction, continuation, and end; by considering the element of text, context, and discourse. The results show how the Eco-Dhamma concept provides solutions related to environmental degradation or damage. The development of the times and the advancement of technology make the environment more uncomfortable due to human behavior in treating the environment which basically acts at will, such as logging motorized vehicles, and so on. The consequences of these human actions cause disasters that are dangerous to himself and the environment, such as floods, landslides, air pollution, and other disasters. Buddhism can contribute to providing understanding while raising human concern for the natural environment.